Okra (Abelmoschus esculentus L. Moench) pod gel as a low-cost alternative to commercial acoustic gel - Alipio, Mark M. (Philippine Journal of Science)
"Ultrasound is an essential diagnostic tool in medicine. However, a commercial acoustic gel is cost-prohibitive, especially in low-resource settings. In this study, okra (Abelmoschus esculentus L. Moench) pod gel was evaluated as a low-cost alternative to commercial acoustic gel by comparing the sonographic image quality, organoleptic characteristics, spreadability, pH, viscosity, and ease of use of commercial gel and formulated okra pod gel. Fresh okra pods were harvested from a local plant nursery"-title page.